Characteristics of Homicidal Cut-Throat Death Cases - Hasan A. Abder-Rahman; Imad M. Al-Abdallat; Lamia Alsenaidi; Mahmoud Zregat; Almotazbellah Abualeme; Huthaifa Ababneh; Abdel-Rahman Al Husni; Abed-Alraheem Ali (Arab Journal of Forensic Sciences & Forensic Medicine)
Cut-throat cases are rare, posing significant challenges for forensic pathologists in determining the manner of death. This study aims to identify key findings that can assist in determining the origin of homicidal intent based on crime scene investigations, the number of wounds, and their characteristics. We conducted a retrospective analysis of 20 cases of homicidal cut-throat injuries in Northern Amman. Detailed examinations of demographic data, toxicological results, neck injuries, other body injuries, and personal motives were performed. The fatal neck wounds were classified by depth into three grades and by location into three levels (upper, middle, lower). The relationships between the level and grade of neck wounds, superficial neck wounds, and other body injuries revealed several patterns distinguishing homicidal cut-throat injuries. This study enhances understanding of the patterns and characteristics associated with homicidal cut-throat injuries, providing valuable insights for forensic investigations.